Analysis of the microbial content of probiotic products commercialized worldwide and survivability in conditions mimicking the human gut environment - Ghelardi, Emilia; Mazzantini, Diletta; Celandroni, Francesco; Calvigioni, Marco; Panattoni, Adelaide; Lupetti, Antonella; Bois De Fer, Beatrice; Perez, Marcos (Frontiers in Microbiology, 2023)
Introduction Probiotics are living microorganisms that, when administered in adequate amounts, confer a health benefit on the host. Adequate number of living microbes, the presence of specific microorganisms, and their survival in the gastrointestinal (GI) environment are important to achieve desired health benefits of probiotic products. In this in vitro study, 21 leading probiotic formulations commercialized worldwide were evaluated for their microbial content and survivability in simulated GI conditions. Methods Plate-count method was used to determine the amount of living microbes contained in the products. Culture-dependent Matrix-Assisted Laser Desorption/Ionization–Time of Flight Mass Spectrometry and culture-independent metagenomic analysis through 16S and 18S rDNA sequencing were applied in combination for species identification. To estimate the potential survivability of the microorganisms contained in the products in the harsh GI environment, an in vitro model composed of different simulated gastric and intestinal fluids was adopted. Results The majority of the tested probiotic products were concordant with the labels in terms of number of viable microbes and contained probiotic species. However, one product included fewer viable microbes than those displayed on the label, one product contained two species that were not declared, and another product lacked one of the labeled probiotic strains. Survivability in simulated acidic and alkaline GI fluids was highly variable depending on the composition of the products. The microorganisms contained in four products survived in both acidic and alkaline environments. For one of these products, microorganisms also appeared to grow in the alkaline environment. Conclusions This in vitro study demonstrates that most globally commercialized probiotic products are consistent with the claims described on their labels with respect to the number and species of the contained microbes. Evaluated probiotics generally performed well in survivability tests, although viability of microbes in simulated gastric and intestinal environments showed large variability. Although the results obtained in this study indicate a good quality of the tested formulations, it is important to stress that stringent quality controls of probiotic products should always be performed to provide optimal health benefits for the host.